2014
DOI: 10.4088/jcp.13m08977
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite, Naturalistic, Observational Study of Transcranial Magnetic Stimulation for Patients With Pharmacoresistant Major Depressive Disorder

Abstract: Objective: Transcranial magnetic stimulation (TMS) is an effective and safe acute treatment for patients not benefiting from antidepressant pharmacotherapy. Few studies have examined its longer term durability. This study assessed the long-term effectiveness of TMS in naturalistic clinical practice settings following acute treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 39 publications
6
93
0
4
Order By: Relevance
“…In large, naturalistic, observational follow up study, TMS demonstrated a sustained durability of effect over 12 months (Dunner et al 2014). To assess long term effectiveness of rTMS therapy patients are currently participating in follow up study.…”
Section: Discussionmentioning
confidence: 99%
“…In large, naturalistic, observational follow up study, TMS demonstrated a sustained durability of effect over 12 months (Dunner et al 2014). To assess long term effectiveness of rTMS therapy patients are currently participating in follow up study.…”
Section: Discussionmentioning
confidence: 99%
“…In the event of a positive test finding, clinicians are encouraged to discuss the findings with the patient and to consider adjunctive treatment options. For example, treatment options such as transcranial magnetic stimulation (TMS) or other neuromodulation interventions may be an augmentation strategy to address treatment non-response (Dunner et al, 2014). Due to the expense and time required to correctly implement such interventions, the PHQ-9 could be used to judiciously allocate scarce and expensive resources.…”
Section: Discussionmentioning
confidence: 99%
“…As such, depression severity is an excellent marker of treatment non-response among heterogeneous patient populations encountered in outpatient and inpatient settings. Accurate identification of individuals at risk of persistent depressive symptoms could lead to more rapid implementation of augmentation strategies to optimize clinical outcomes (Dunner et al, 2014;Holtzheimer and Mayberg, 2012). Biologically-based strategies for early identification of treatment resistant depression (TRD) have been explored including: neuroimaging (Konarski et al, 2009;Mayberg et al, 1997;Siegle et al, 2006Siegle et al, , 2012Stroup et al, 2006), genetic (Ising et al, 2009, Uher et al, 2009, electroencephalographic (Leuchter et al, 2009), and immune-related measures (Raison et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that antidepressant benefits of TMS can persist on the order of months (66,67), but relatively few studies have addressed optimal relapse prevention strategies to sustain benefits. Available evidence suggests that antidepressant initiation is critical to maintain remission (68).…”
Section: Transcranial Magnetic Stimulation Tms In Major Depressive DImentioning
confidence: 99%